The epidemiology and the pathogen distribution of pediatric dacryocystitis in Chinese population 2017-2022 - Zhihong Sun; Mingchao Li; Huiqing Sun (BMC, 2024)
Abstract Background Dacryocystitis is a common disease in pediatric ophthalmology. Analysis of basic information, flora distribution, and characteristics of information on drug-resistant bacteria in children with dacryocystitis for 6 years, providing evidence for ophthalmologic infection prevention and clinical management strategies. Methods A retrospective cohort study was conducted to evaluate the demographics of dacryocystitis in children and microbiological characteristics of secretion cultures, and to analyze the basic information, distribution of pathogenic bacteria, drug resistance, and to plot trendsand distribution pie charts according to the years. Results This study recruited 5791 specimens. Decreased incidence of dacryocystitis from 2020 to 2022 (including the COVID-19 pandemic). The age of highest incidence of dacryocystitis is infancy, followed by the neonatal period, and the incidence decreased with age. Streptococcus pneumoniae had the highest percentage in 2017, and the overall trend was decreasing, the difference was statistically significant (p < 0.001); Streptococcus mitis showed an overall increasing trend, with the highest incidence in 2022 and the lowest in 2017, with a statistically significant difference (p < 0.001); Haemophilus influenzae was the most common gram-negative bacteria with an overall decreasing trend (p < 0.001); The incidence of Catamoeba and Stenotrophomonas varied from year to year, with statistically significant differences (p = 0.010, p = 0.033, respectively). Methicillin-resistant Staphylococcus aureus (MRSA) had the lowest incidence in 2017 and 2022 the highest incidence in 2022, with a statistically significant difference in incidence between years (p = 0.003); β-lactamase-positive was the most common type of resistance, and MRSA was the second, with statistically significant differences between years (p = 0.003, p < 0.001, respectively). Streptococcus pneumoniae is a common etiologic agent of dacryocystitis in all age groups. Conclusions Dacryocystitis in children is significantly associated with age characteristics and infection-related pathogens, and infection prevention and control can help reduce the infection of related pathogens and the increase of new drug-resistant strains. Close monitoring of changes in pathogen distribution in ocular secretion cultures can help in early intervention and treatment of infectious dacryocystitis.